Monetary Penalties and Noncompliance with Environmental Laws: a Mediation Analysis - Barrett, Kimberly L. (American journal of criminal justice, 2018)
Studies that assess the impact of monetary penalties on environmental compliance have yielded mixed results. While some studies suggest fines deter future violations other studies find that fines do little to encourage compliance. This longitudinal study examines the impact of the dollar amount of fines on compliance with environmental laws among major facilities in the state of Michigan ( n = 37). Results from a mediation analysis suggest that while noncompliance may slightly decrease immediately following a fine there are few changes to a firm’s long term compliance behavior. Furthermore, analyses of these data suggest that total fines levied prior to the most recent fine actually have a positive relationship with noncompliance. We suggest these results imply a decaying effect of deterrence that is perhaps connected to the organizational structure of the treadmill of production.